Galactomannan Test in Suspected Invasive Pulmonary Aspergillosis Patients: An Evidence-Based Case Report - Rahmiati, Lina; Prasetyo, Dimas Seto; Mubarokah , Mubarokah (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Invasive pulmonary aspergillosis is a severe fungal infection with a high mortality rate. However, because the clinical and radiological images are non-specific, and culture results take a long time and yield unsatisfactory results, rapid, high-accuracy tests are needed. Consequently, the diagnosis of invasive pulmonary aspergillosis remains difficult. The objective of this study was to assess the galactomannan (GM) test as a diagnostic tool for patients with suspected invasive pulmonary aspergillosis. Methods: Articles were searched through three databases (PubMed, Embase, and Cochrane) using keywords based on PICO components related to suspected invasive pulmonary aspergillosis and the GM test. Titles and abstracts were screened, duplicates were removed, and articles were filtered according to inclusion and exclusion criteria. The critical appraisal was performed using methods recommended by the Center for Evidence-Based Medicine at the University of Oxford. Results: Three studies reported serum GM test sensitivities ranging from 71% to 88%, suggesting that this assay may be suitable as a screening tool due to its adequate true positive detection rate. The specificity values in these studies ranged from 89% to 98%, indicating good accuracy in correctly identifying true negative cases. However, considerable heterogeneity was observed across the studies. Conclusion: The GM test is a promising rapid diagnostic tool for suspected invasive pulmonary aspergillosis, enabling earlier and more accurate antifungal treatment. However, further studies are needed to standardize its cut-off values and interpretation to ensure consistent clinical application.